PENGARUH PENGGUNAAN TEPUNG DAUN PEPAYA (Carica Papaya l) SEBAGAI PENGGANTI SEBAGIAN RANSUM BASAL TERHADAP PERSENTASE KARKAS DAN PERSENTASE LEMAK ABDOMEN AYAM PEDAGING - Surah, Marsela; Sompie, Florencia N.; Kowel, Youdhie H. S.; Imbar, Meity R. (ZOOTEC, 2020)
THE EFFECT OF THE USE OF PAPAYA LEAVES SUBSTITUTED TO BASAL DIET ON THE PERCENTAGE OF CARCASS AND ABDOMINAL FAT PERCENTAGE OF BROILER CHICKEN. This study aims to determine the effect of papaya leaf meal substituted to basal diet on the carcass weight, percentage of carcass, and abdominal fat of broilers. This study used 80 unsexed broilers, day old chick (DOC). The experiment used a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The arrangement of the experimental treatments was as follows: Râ‚€ = 100% basal diet (BD), 0% papaya leaf meal (PLM), Râ‚ = 95% BD + 5% PLM, Râ‚‚ = 90% BD + 10% PLM, Râ‚ƒ = 85% BD + 15% PLM. The results showed that partial replacement of the basal diet with with papaya leaf meal had no significant effect on carcass weight and the percentage of broiler abdominal fat. The treatment gave a very significant difference on the percentage of carcass. On carcass percentage results showed that R0 was highly significant different from R3 but not significantly different with R2 and R1. Treatment R1 was significantly different from R3 but not significantly different from R2, whereas between treatments R2 and R3 were significantly different. Based on the results of this study it can be stated that the use of papaya leaf meal up to level of 15% can produce a good proportion of carcass and abdominal fat.Â Keywords: broiler, papaya leaf meal, carcasses, abdominal fat.